A empreendedora está on: vivência de mulheres ao empreenderem nas redes sociais virtuais - Tavares, Nayane do Vale (2023)
This study aimed to understand how women experience digital entrepreneurship, based on the reasons present in their entrepreneurial action, in virtual social networks, in the light of Schutz's social phenomenology (1975, 1979). The study was carried out with entrepreneurs who had stores exclusively online on Instagram, seeking to highlight their daily lives, experiences and acquired experiences. This is an exploratory study, with a qualitative approach, through field research, following a semi-structured interview script. The data organization and analysis technique followed Bardin's (2011) content analysis model. The results showed that the majority of digital entrepreneurs started their businesses motivated by opportunity, seeking flexibility/freedom, satisfaction and fulfillment, even in the pandemic context. In their experiences, the public highlighted that they had not acquired loans from banks, were overloaded with tasks and had difficulty reconciling professional and personal demands but stated that they had a good support network. Regarding Instagram, advantages were highlighted for its use: easy handling, free, good publicity, high visibility and overcoming geographical barriers. The challenges include working with digital marketing, paid traffic and organizing time to manage content. Future expectations are to continue being digital entrepreneurs, making use of online platforms.